Pengaruh Disiplin Kerja, Motivasi Kerja dan Lingkungan Kerja Terhadap Kepuasan Kerja Karyawan dan Guru: Studi pada Sekolah Menengah Pertama (SMP) Muhammadiyah 7 Semarang - Riskha Septi Prahesti; Tristiana Rijanti (Pusat Riset dan Inovasi Nasional, 2025)
This research aims to determine the impact of work discipline, motivation, also environment on employee and teacher job satisfaction at Muhammadiyah 7 Junior High School, Semarang. A total of 81 respondents participated in this study. By utilizing primary data through questionnaire-based data collection. The study population included employees and teachers at Muhammadiyah 7 Junior High School, Semarang, by using purposive sampling technique. Testing the results of multiple linear regression analysis using SPSS version 25. The questionnaire was tested for validity and reliability. Multiple linear regression tests include model testing and hypothesis testing. The results obtained from ongoing research indicate that work discipline has a negative influence on job satisfaction, work motivation has a positive influence on job satisfaction, and the work environment has a positive influence on job satisfaction.